Regenerative Therapy Approaches and Encountered Problems in Sensorineural Hearing Loss - Kelleci, Kuebra; Golebetmaz, Eda (BENTHAM SCIENCE PUBL LTD, 2023)
Hearing loss is one of the most important public health matters worldwide, severely affecting people's social, psychological, and cognitive development. The perception of sound, movement, and balance in vertebrates depends on a special sensory organ called the cochlea, which contains hair cells and supporting cells in the inner ear. Genetic factors, epigenetics, the use of ototoxic drugs (some antibiotics and chemotherapeutics), noise, infections, or even aging can cause loss of hair cells and their related primary neurons, leading to sensorineural hearing loss. Although a sensorineural hearing loss, also known as permanent hearing loss, is treated with hearing aids and cochlear implants, treatment methods are limited. Since even the best implant cannot exhibit the characteristics of the original ear, the permanent sensory deficit will be permanent. For this reason, it has become important to develop regenerative treatment methods to regenerate and replace lost or damaged hair cells and neurons. Developments in stem cell technology have led to promising studies in regenerating damaged/lost hair cells or neurons with endogenous or exogenous cell-based therapies. Epigenetic mechanisms can turn hearing-related genes on and off and determine which proteins to copy. In addition, due to gene silencing, gene replacement, and CRISPR/CAS9 technology, gene therapy methods have accelerated, and studies have been carried out to treat dominant and recessive mutations that cause genetic-induced hearing loss or increase hair cell regeneration. In this paper, potential gene therapy and stem cell applications in the acquisition of cochlear function, which causes sensorineural hearing loss, and the difficulties encountered in these applications are compiled from a bioengineering perspective.
Keywords: Hair cell; iPSC; regeneration; hearing loss; stem cell transplantation; gene therapy; epigenetic; MESENCHYMAL STEM-CELLS; AUDITORY HAIR-CELLS; SPIRAL GANGLION NEURONS; GENE DELIVERY; IN-VITRO; MEDIATED DELIVERY; MAMMALIAN COCHLEA; RNA INTERFERENCE; SUPPORTING CELLS; NERVOUS-SYSTEM; Cell Biology